المقاصد الكلية فى العمل الخيرى - العنزي، سعد بن مقبل بن عيسى الحريري Alenzi, Saad Bin Muqbel Bin Issa Alhariri (مجمع الفقه الإسلامي بالهند, 2019)
هذا البحث عنوانه (المقاصد الكلية في العمل الخيري)، ويقوم على ركيزتين: الأولى: علم المقاصد الشرعية، وخصوصا (المقاصد الكلية). الثانية: استثمار هذا العلم في تحرير مقاصد كلية للعمل الخيري. وجاء البحث في خمسة مباحث: المبحث الأول: مقصد حفظ الدين، وأثره في العمل الخيري. المبحث الثاني: مقصد حفظ النفس، وأثره في العمل الخيري. المبحث الثالث: مقصد حفظ العقل، وأثره في العمل الخيري. المبحث الرابع: مقصد حفظ النسل، وأثره في العمل الخيري. المبحث الخامس: مقصد حفظ المال، وأثره في العمل الخيري. ثم خاتمة البحث. وقد وقع في أعطاف هذا البحث شرح كل مقصد، والتدليل عليه بالنصوص الشرعية، وأقوال العلماء، ثم ربط ذلكم المقصد بالعمل الخيري. وأهم نتائج البحث: الأولى: إثبات مركزية حفظ الدين في العمل الخيري، وكونه مقصدا كليا فيه، وأعظم ضمانة لاستمراره، وصموده، وتميزه. الثانية: تقرير تجذر حفظ الكليات الخمس في العمل الخيري، وسعة تأثيرها في نشاط المسلمين أفرادا وجماعات. الثالثة: بيان التكامل المنهجي والمعرفي والسلوكي في العمل الخيري الإسلامي، وأن تحقيق ذلك سببه وباعثه؛ مراعاة المقاصد الكلية في الشريعة الإسلامية.
This research is titled "The Purposes of Charity" and is based on two pillars: The first is the knowledge of the legitimate purposes, especially the total objectives. Second: the investment of this science in the liberation of the purposes of college for charitable work. The research came in five sections: The first topic: the purpose of preserving religion, and its impact on charitable work. The second topic: the purpose of self preservation, and its impact on charitable work. The third topic: the purpose of preserving the mind, and its impact on charitable work. The fourth topic: the purpose of conservation of the offspring, and its impact on charitable work. The fifth topic: the purpose of saving money, and its impact on charitable work. Then finish the search. In this research, the explanation of each destination, and its evidence by the legal texts, and the statements of the scholars, were then signed and linked to charitable work. The most important search results: The first is to prove the centrality of the preservation of religion in charitable work, and as a whole destination in it, and the greatest guarantee for its continuity, steadfastness and excellence. Second: the report of the root of the preservation of the five colleges in charitable work, and the extent of its impact on the activity of Muslims, individuals and groups. Thirdly, a statement of systematic, cognitive and behavioral integration in the Islamic charitable work, and that this is achieved by reason and its motivation
Keywords: علم المقاصد الشرعية -- المقاصد الكلية -- العمل الخيرى -- الشريعة الإسلامية